RECONHECIMENTO DA FALA SUBVOCAL BASEADO EM ELETROMIOGRAFIA DE SUPERFÍCIE (EMG) UTILIZANDO ANÁLISE DE COMPONENTES INDEPENDENTES (ICA) E REDE NEURAL MLP - Mendes, José da Assunção Gomes (2007)
The performance of speech recognition systems is commonly degraded by either speech-related disabilities or by real-world factors such as the environment s noise level and reverberation. In this research, we propose a subvocal speech recognition system based on electromyography (EMG signal) for subvocal acquisition, Independent Component Analysis (ICA) for feature extraction and Neural Networks MLP for classification. We have evaluated the system s performance using a subvocal vowel phonemes database. According to the results, the methodology proposed obtained a success rate of 93.99%.